Optimization of Sago Dregs as Pellet Feed of Broiler in Tanjung Meranti Islands Village: Optimalisasi Ampas Sagu Sebagai Pakan Pellet Ayam Broiler Di Desa Tanjung Kepulauan Meranti - Bakhendri Solfan; Elfi Rahmadani; Anwar Harahap; Muhamad Rodiallah; Jepri Juliantoni; Triani Adelina; Dewi Ananda Mucra; Evi Irawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Tanjung Kepulauan Meranti Village, Riau has production large sago plants so that the waste is used as animal feed with pellet technology. The purpose of this service to utilize sago pulp that has not been used as feed of broiler. The service method uses PAR, which is a method of involving community groups as whole in research activities so that positive social change occurs. The results show that community groups are very enthusiastic about participating in community service activities with indicators the ease with which community groups understand the material provided. Some of the material conveyed that sago pulp can be fermented to increase nutritional value, especially protein and reduce crude fiber, then fermented sago pulp can be used as broiler feed pellets. In conclusion, sago pulp can be used as a pellet product at a low price as an alternative to commercial pellet feed to reduce costs in broiler farming